Convection and surface tension profiles for aqueous droplet under microwave radiation - Kanazawa, Y.; Asada, M.; Asakuma, Y.; Honda, I.; Phan, Chi; Parmar, Harisinh Bhikhubhai; Pareek, Vishnu; Evans, G. (SPIE, 2014)
Surface tension of fluid is crucial for multiphase systems and is often manipulated during industrial processes by introducing surfactants. In this study, effect of microwave radiation on surface tension of aqueous solution was investigated for new physical method to manipulate the surface tension without using chemicals. It has found that surface tension profiles of aqueous solution during microwave are different with the salt concentration. Moreover, convections in the droplet during microwave radiation were compared to provide new understanding on the non-thermal effect of microwave.